Working memory task performance in a simulated peripheral sensory-motor deficit. - Gafoor, Shezeen; Jagadeesh, Anoop; Uppunda, Ajith (Journal of the All India Institute of Speech & Hearing)
Purpose: The study observed the effects of oral anesthesia (a simulated sensory-motor deficit) on auditory working memory task performance. Materials and Methods: In a total of 19 neurotypical young adults, we compared backward digit (BD) spans measured when the primary oro-motor structures were anesthetized (sensory-motor deficit simulation) with those measured without the oral anesthetic (control condition). In a subsequent experiment on a subset of the participants, we also measured the rate of speech (words per second) in the two conditions. Result: Paired t tests showed that anesthetization of the oro-motor structures significantly reduced performance in both the BD span and the rate of speech experiments in our participants. Conclusions: The worsening of both BD spans (likely due to the affected rehearsal mechanism) and rate of speech (likely due to the sluggish movement of the articulators as an aftereffect of the oral anesthesia) reinforce the notion that sensory-motor feedback achieved via subvocal articulatory rehearsals, a constituent of the phonological loop of the working memory system, contributes to the individuals' working memory task performances.